Preparation and physicochemical properties of modified jackfruit starches - Ornanong S. Kittipongpatana (2018)
Modifications of jackfruit starch, extracted from the cotyledons of Artocarpus heterophyllus Lam. (Thong Prasert cultivar), were carried out to obtain a pregelatinized starch, three (m-, n- and i-) carboxymethyl starches, a hydroxypropyl starch and a phosphate cross-linked starch. Physicochemical properties of native and modified jackfruit starches were comparatively investigated. Pregelatinized, hydroxypropyl, and cross-linked starches were insoluble or partially soluble in water at room temperature, while carboxymethyl starches were soluble with good overall water uptake. Scanning electron microscopic images revealed that granules of most modified jackfruit starches retained the native appearance and crystal structure, with the exception of pregelatinized starch and two (n- and i-) carboxymethyl starches, which showed significant breakage of granules. X-ray diffraction patterns corroborated to suggest the loss of crystallinity in these modified starches. Thermal analysis showed a significant decrease in the gelatinization temperature of hydroxypropyl starch with no change in enthalpy, while higher gelatinization temperature and less enthalpic value were observed for pregelatinized starch. Pregelatinized and hydroxypropyl starches showed temperature-dependent improvement on swelling and solubility, while cross-linked starch exhibited less solubility. Aqueous solution of m-carboxymethyl starch yielded the highest apparent viscosity with improved heating-cooling stability. © 2011 Elsevier Ltd.